Faktor – Faktor Yang Mempengaruhi Lama Mencari Kerja Tenaga Kerja Terdidik Pada Pemerintahan Kota Prabumulih - LIANA, LIANA MARISKA; FAUZIAH, FAUZIAH ASYIEK; AZIZAH, AZIZAH HUSIN (I-Economics, 2016)
The high level of employment in the formal sector in Prabumulih which reached 49. 709 people or 73.62 percent of the educational level make sense that an educated workforce is in Prabumulih constantly increasing. For a new city and start his career begin to develop an increasing number of educated manpower was increased to a positive meaning for Prabumulih city. It has 6 districts of Prabumulih city, based on six sub-districts, one district was Cambai. Cambai is the center of government agencies Prabumulih which has a total workforce of the most educated compare to other agencies, with the number of educated workforce of 412 people or 34.51 percent, one of the processes to see labor timeout is Government is working on Prabumulih as employees mostly seen from the last education level. Another factor affecting the long search of work are age and work experience. Productive age will usually assigned the job opportunities more quickly than age who has passed their productive age. Additionally, revenue will also be crucial for educated job seekers to find a job due to the corresponding revenue to make ends meet could be one parameter length of a person to obtain employment. This study aims to identify factors - factors that affect the long search for an educated workforce working in Government Prabumulih.Methods:This study uses quantitative methods. Sampling proportionally stratified random sampling. Sample of 100 respondents educated workforce have civil service men and women who worked on Government Prabumulih. The study used multiple linear regression test.Results: The results showed that education is the factor most affecting longer seeking employment educated workforce with a significance of 0.000.Conclusion:There are three factors that affect the long educated workers seeking work in cities Prabumulih namely education, age, and income. Based on t-test analysis showed partial factors affecting education in the long search for employment for educated labor in the Government Prabumulih.Keywords: duration of looking for work, labor, educated workforce